School connectedness and child anxiety. Issue 1 (3rd March 2020) - Pikulski, Paige J.; Pella, Jeffrey E.; Casline, Elizabeth P.; Hale, Amy E.; Drake, Kelly; Ginsburg, Golda S.
Abstract: Poor school connectedness (SC), defined as students' feelings of belonging, safety, and fairness at school, is a risk factor for negative psychosocial outcomes. Few studies have examined the specific relationship between SC and anxiety. This study examined the relation between SC and anxiety within a group of 114 clinically anxious youth (mean age = 10.82; SD = 2.93; 48.2% female; 70.2% White, non-Hispanic); age differences were also examined. Results indicated that SC was significantly negatively associated with age but unrelated to gender, race/ethnicity, socio-economic status, parent education, or presence of a comorbid disorder. Findings generally revealed that low SC was associated with greater total and domain specific anxiety. SC may play a unique role in the maintenance of global and domain specific anxiety symptoms.